Interactive storytelling : 8th Joint Conference on Interactive Digital Storytelling, ICIDS 2015, Copenhagen, Denmark, November 30-December 4, 2015, proceedings /: 8th Joint Conference on Interactive Digital Storytelling, ICIDS 2015, Copenhagen, Denmark, November 30-December 4, 2015, proceedings. (2015) - Unknown
No abstract available